Subsystem trace-distances of two random states. (28th April 2023) - Telles de Miranda, Joaquim; Micklitz, Tobias
Abstract: We study two-state discrimination in chaotic quantum systems. Assuming that one of two N -qubit pure states has been randomly selected, the probability to correctly identify the selected state from an optimally chosen experiment involving a subset of N − N B qubits is given by the trace-distance of the states, with N B qubits partially traced out. In the thermodynamic limit N → ∞, the average subsystem trace-distance for random pure states makes a sharp, first order transition from unity to zero at f = 1 / 2, as the fraction f = N B / N of unmeasured qubits is increased. We analytically calculate the corresponding crossover for finite numbers N of qubits, study how it is affected by the presence of local conservation laws, and test our predictions against exact diagonalization of models for many-body chaos.